Análisis De Hallazgos Histopatológicos En Paloma Domestica (Columbia Livia) Provenientes De La Plaza De Bolívar, Bogotá D.C (2021)
Pigeons (Columba livia) are a cultural part of the historic centers of the great cities of the world, among them the Plaza de Bolivar in the city of Bogotá, Colombia, without However, they are an invasive species that can become a threat to human health. of visitors (Redondo, Vega & Forero, 2018). The domestic pigeon is a species considered as part of the fauna of many urban areas, so that its The population has been growing exponentially around the world. Currently, it is considered a plague due to the damage that its feces generates in the buildings and historical monuments, as well as for the possibility of being able to transmit diverse diseases of public health importance (Arias, Morales & Villacaqui, 2017). Those people who are in direct contact with birds are exposed to diseases Therefore, appropriate hygiene and handling measures must be taken for birds that corresponds, since it is a vector of contagion and global influence, its The consequences can be serious without proper management. (Andrade & Diaz, 2015). Pigeons (Columba livia) are a cultural part of the historic centers of the great cities of the world, among them the Plaza de Bolivar in the city of Bogotá, Colombia, without However, they are an invasive species that can become a threat to human health. of visitors (Redondo, Vega & Forero, 2018). The domestic pigeon is a species considered as part of the fauna of many urban areas, so that its The population has been growing exponentially around the world. Currently, it is considered a plague due to the damage that its feces generates in the buildings and historical monuments, as well as for the possibility of being able to transmit diverse diseases of public health importance (Arias, Morales & Villacaqui, 2017). Those people who are in direct contact with birds are exposed to diseases Therefore, appropriate hygiene and handling measures must be taken for birds that corresponds, since it is a vector of contagion and global influence, its consequences can be serious without proper management. (Andrade & Diaz, 2015).